2023
DOI: 10.1021/acs.jafc.3c02497
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Natural Sesquiterpene Lactone 1-O-Acetylbritannilactone Analogues Bearing Oxadiazole, Triazole, or Imidazole Scaffolds for the Development of New Fungicidal Candidates

Abstract: In recent decades, natural products have been considered important resources for developing of new agrochemicals because of their novel architectures and multibioactivities. Consequently, herein, 1-O-acetylbritannilactone (ABL), a natural sesquiterpene lactone from Inula britannica L., was used as a lead for further modification to discover fungicidal candidates. Six series of ABL-based derivatives containing an oxadiazole, triazole, or imidazole moiety were designed and synthesized, and their antifungal activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Furthermore, current research reveals that regardless of the inhibitor type, be it organic small molecules, peptides, or proteins, as well as the different target sites (histone deacetylase, succinate dehydrogenase, pyruvate kinase), inhibitors consistently exhibit a more pronounced inhibitory effect on spore germination rather than mycelium growth in B. cinerea . The results of this study are entirely consistent with the literature, suggesting that the observed variations in inhibition effects are not directly associated with the Chitinase target of the DBA inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, current research reveals that regardless of the inhibitor type, be it organic small molecules, peptides, or proteins, as well as the different target sites (histone deacetylase, succinate dehydrogenase, pyruvate kinase), inhibitors consistently exhibit a more pronounced inhibitory effect on spore germination rather than mycelium growth in B. cinerea . The results of this study are entirely consistent with the literature, suggesting that the observed variations in inhibition effects are not directly associated with the Chitinase target of the DBA inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…Following incubation at 26 °C for 4 days, the mycelium discs were measured, and the therapeutic effects were calculated. The formulas were calculated as Therapeutic .25em effect false( % false) = normalC normalT normalC 1 × 100 where C represents the diameter of B. cinerea growth on blank control and T represents the diameter of B.…”
Section: Methodsmentioning
confidence: 99%
“…In vivo, the activity of HWY-289 against B. cinerea was assayed by a previously reported method with minor modifications . We tested ripe, healthy, similarly shaped tomatoes from a local supermarket.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations